miR-16 Targets Transcriptional Corepressor SMRT and Modulates NF-kappaB-Regulated Transactivation of Interleukin-8 Gene - Zhou, Rui; Li, Xiaoqing; Hu, Guoku; Gong, Ai-Yu; Drescher, Kristen M.; Chen, Xian-Ming (PLOS ONE, 2012)
The signaling pathways associated with the Toll-like receptors (TLRs) and nuclear factor-kappaB (NF-κB) are essential to pro-inflammatory cytokine and chemokine expression, as well as initiating innate epithelial immune responses. The TLR/NF-κB signaling pathways must be stringently controlled through an intricate network of positive and negative regulatory elements. MicroRNAs (miRNAs) are non-coding small RNAs that regulate the stability and/or translation of protein-coding mRNAs. Herein we report that miR-16 promotes NF-κB-regulated transactivation of the IL-8 gene by suppression of the silencing mediator for retinoid and thyroid hormone receptor (SMRT). LPS stimulation activated miR-16 gene transcription in human monocytes (U937) and biliary epithelial cells (H69) through MAPK-dependent mechanisms. Transfection of cells with the miR-16 precursor promoted LPS-induced production of IL-8, IL-6, and IL-1α, without a significant effect on their RNA stability. Instead, an increase in NF-κB-regulated transactivation of the IL-8 gene was confirmed in cells following transfection of miR-16 precursor. Importantly, miR-16 targeted the 3′-untranslated region of SMRT and caused translational suppression of SMRT. LPS decreased SMRT expression via upregulation of miR-16. Moreover, functional manipulation of SMRT altered NF-κB-regulated transactivation of LPS-induced IL-8 expression. These data suggest that miR-16 targets SMRT and modulates NF-κB-regulated transactivation of the IL-8 gene.